Incidence of Idiopathic Ventricular Arrhythmias: A Population-Based Study. (February 2017) - Sirichand, Surksha; Killu, Ammar M.; Padmanabhan, Deepak; Hodge, David O.; Chamberlain, Alanna M.; Brady, Peter A.; Kapa, Suraj; Noseworthy, Peter A.; Packer, Douglas L.; Munger, Thomas M.; Gersh, Bernard J.; McLeod, Christopher J.; et al.
Abstract : Background—: Ventricular tachycardia and premature ventricular complexes (PVCs) most frequently occur in the context of structural heart disease. However, the burden of idiopathic ventricular arrhythmias (IVA) in the general population is unknown. Methods and Results—: We identified incident cases of IVA between 2005 and 2013 from Olmsted County, Minnesota, using the Rochester Epidemiology Project database. For PVC cohorts, we included those with frequent (defined as ≥100 PVC/24 hours) symptomatic PVCs. We defined IVA-associated cardiomyopathy as a drop in ejection fraction of ≥10% from baseline. Between 2005 and 2013, we identified 614 individuals with incident IVA (229 [37.3%] were male; average age was 52.1±17.2 years). Of these, 177 (28.8%) had idiopathic ventricular tachycardia, 408 (66.5%) had symptomatic PVCs, and 29 (4.7%) had IVA-associated cardiomyopathy. The age- and sex-adjusted incidence rates in 2005 to 2007, 2008 to 2010, and 2011 to 2013 were 44.9 per 100 000 (95% confidence interval [CI], 38.0–51.8), 47.6 per 100 000 (95% CI, 40.8–54.5), and 62.0 per 100 000 (95% CI, 54.4–69.6), respectively. In idiopathic ventricular tachycardia, there was an increase in incidence rate with ages ( P <0.001) but not between sexes ( P =0.12). The age-adjusted incidence of symptomatic PVC was higher in females than in males (46.2 per 100 000 [95% CI, 40.9–51.6] versus 20.5 per 100 000 [95% CI, 16.8–24.3]; P <0.001). The small number of individuals with IVA-associated cardiomyopathy precluded any formal testing. Conclusions—: The incidence of IVA is increasing. Furthermore, overall incidence increases with age. Although the rate of idiopathic ventricular tachycardia is similar across sexes, women have a higher incidence of symptomatic PVC. Abstract : Supplemental Digital Content is available in the text.